COMPARISON OF STATE‐MANAGED AND FARMER‐MANAGED IRRIGATION SYSTEMS IN PUNJAB, PAKISTAN1. (14th September 2014) - Latif, Muhammad; Haq, Zia‐Ul; Nabi, Ghulam
ABSTRACT Irrigation system management in Pakistan is undergoing institutional reforms to implement participatory irrigation management (PIM) with the involvement of farmers. This study was undertaken to examine the impacts of institutional reforms by comparing the irrigation service delivery of Hakra 3‐R distributary operated by the provincial irrigation department, and Hakra 4‐R distributary operated by the farmers' organization (FO). The present study is based on detailed analysis of 18 watercourses, 9 on each of the secondary canal (distributary). The investigations were focused on parameters such as delivery performance ratio (DPR), spatial coefficient of variation (CVS), temporal coefficient of variation (CVT), farmers' net income and land and water productivities. Results of the study revealed that the 4‐R distributary has a relatively superior irrigation service delivery in comparison to the 3‐R distributary. Average net income, land and water productivities were higher on the 4‐R distributary than the 3‐R distributary. Based on the results of this study, it is concluded that the overall performance of the FO‐managed irrigation canal (4‐R) was better than the state‐managed canal (3‐R), but the performance of the former was also below expectations. Copyright © 2014 John Wiley & Sons, Ltd.